Alcoholysis kinetics and mechanism studies of ethyl levulinate production from ball milled corn stover. Issue 53 (29th November 2022) - Liu, Huan; Meng, Haibo; Cong, Hongbin; Shen, Xiuli; Chen, Xueli; Xing, Haohan; Dai, Jinhang
Abstract : Kinetic analysis of ethyl levulinate (EL) production from ball-milled corn stover catalyzed by Brønsted (B) acidic ionic liquid [Bmim-SO3 H][HSO4 ] (SO3 H-IL) and Lewis (L) acidic Al2 (SO4 )3 was performed in this study. Abstract : Alcoholysis of ball-milled biomass over catalysts with Brønsted and Lewis acid sites provides an efficient and sustainable scheme to produce versatile biobased chemicals under mild conditions; however, optimizing the process parameters is challenged by the complexity of reaction pathways and the multiplicity of ball milling and combination catalyst gains. To address these challenges, we present kinetic analysis of ethyl levulinate (EL) production from ball-milled corn stover catalyzed by Brønsted (B) acidic ionic liquid [Bmim-SO3 H][HSO4 ] (SO3 H-IL) and Lewis (L) acidic Al2 (SO4 )3 . Product analysis shows that cellulosic substrates can form EL either through the intermediate ethyl-d -glycopyranoside (EDGP) or levoglucosenone (LGO), with the former leading the alcoholysis reaction. Kinetics results reveal that ball milling accelerates the reaction rate by promoting the formation of EDGP and LGO from cellulose. Pure SO3 H-IL gives high selectivity towards EDGP from ball-milled corn stover and promotes the LGO production, whereas addition of Al2 (SO4 )3 substantially facilitates their further conversion to EL. Our findings contribute to the rational design of efficient catalytic strategies for sustainable and profitable biorefinery.